2019
DOI: 10.5551/jat.44107
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake during 56 Weeks of a Low-Fat Diet for Lomitapide Treatment in Japanese Patients with Homozygous Familial Hypercholesterolemia

Abstract: Aim:Lomitapide is an oral inhibitor of the microsomal triglyceride transfer protein used to treat homozygous familial hypercholesterolemia (HoFH); patients require a low-fat diet to minimize gastrointestinal adverse effects and dietary supplements to prevent nutrient deficiencies. We investigated the diet and nutritional status during lomitapide treatment. Methods: Japanese patients with HoFH, who were in a phase 3 trial of lomitapide, were instructed to start low-fat diets with supplements of vitamin E and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Interestingly, treatment of HFD mice with lomitapide significantly decreased body weight and the percentage of fat mass and increased the percentage of lean mass in comparison to mice on HFD alone. Our findings are in accordance with a previous clinical study conducted with Japanese patients showing that treatment with lomitapide significantly induced a decrease in body weight (26). A phase 3 study of lomitapide treatment in patients with HoFH showed that decreased body weight was not associated with energy expenditure or food intake changes (27).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, treatment of HFD mice with lomitapide significantly decreased body weight and the percentage of fat mass and increased the percentage of lean mass in comparison to mice on HFD alone. Our findings are in accordance with a previous clinical study conducted with Japanese patients showing that treatment with lomitapide significantly induced a decrease in body weight (26). A phase 3 study of lomitapide treatment in patients with HoFH showed that decreased body weight was not associated with energy expenditure or food intake changes (27).…”
Section: Discussionsupporting
confidence: 93%
“…A study was conducted in HoFH patients in Japan, and it is now on the market 99) . However, since the frequencies of adverse events such as fatty liver and diarrhea are high with MTP inhibitor, it is essential to strictly control fat and alcohol intake 100) . Probucol reportedly exerts a certain Blood access in lipoprotein apheresis is common via the cubital or brachial vein.…”
Section: Drug Therapy In Hofhmentioning
confidence: 99%
“…Our data are in agreement with a clinical study conducted on Japanese patients with HoFH. In this study, the treatment with lomitapide significantly decreased the body weight of the patients [ 49 ]. Additionally, in Zucker fatty rats, lomitapide treatment decreased their body weight and food intake, this was accompanied by a significant improvement in glucose tolerance [ 36 ].…”
Section: Discussionmentioning
confidence: 99%